Hubungan Motivasi dan Kemandirian Belajar: Pentingnya Bahasa Indonesia untuk Tujuan Akademik di Perguruan Tinggi - Lakawa, Agustin Rebecca; Zulfadhli, Muhammad; Hamdani, Haris (Program Studi Pendidikan Bahasa dan Sastra Indonesia FKIP Universitas Islam Riau, 2024)
Motivation and learning autonomy determine the level of success in learning languages; even the relationship between the two is considered to affect each other. Learning Indonesian for academic purposes is still underdeveloped at the university level regarding student motivation and learning autonomy. Therefore, understanding both terms can accommodate all parties involved in the learning process toward students' strategies, styles, and needs. This study investigates how the relationship between motivational constructs and autonomy contributes to the sustainability of the Indonesian learning process with academic purposes in higher education. This qualitative study was conducted among 34 undergraduate students who took the general basic Indonesian course at Universitas Trisakti Jakarta. Data was collected using a questionnaire distributed using google form and calculated using a Likert scale of 1 to 4, from strongly agree to strongly disagree to measure the extent to which students show their level of motivation and autonomy in learning academic Indonesian. The results of this study show that the majority of students have instrumental motivation, namely to obtain the passing grade required by Indonesian language course. This answer is closely related to students' belief which is obtained in the Indonesian language course that can help them in facing various tasks in other courses in terms of using academic Indonesian. Regarding learning autonomy, students identified among others, ability, responsibility, and confidence in directing the learning process. This study concludes that students show high motivation and proportionally equal to their learning autonomy.